Effects of Fine-Grained Particles' Migration and Clogging in Porous Media on Gas Production from Hydrate-Bearing Sediments. (23rd May 2019) - Jung, Jongwon; Kang, Hongsig; Cao, Shuang Cindy; Al-Raoush, Riyadh I.; Alshibli, Khalid; Lee, Joo Yong
Abstract : The migration of fine particles in porous media has been studied for different applications, including gas production from hydrate-bearing sediments. The clogging behavior of fine particles is affected by fine particle-pore throat size ratio, fine particle concentration, ionic concentration of fluids, and single/multiphase fluid flow. While previous studies presented valuable results, the data are not enough to cover a broad range of particle types and sizes and pore throat size in natural hydrate-bearing sediments. This paper presents a novel micromodel to investigate the effects of fine particle-pore throat size ratio, fine concentration, ionic concentration of fluid, and single/multiphase fluid flow on clogging or bridging in porous media. The results show that (1) the concentration of fine particles required to form clogging and/or bridging in pores decreased with the decrease in fine particle-pore throat size ratio, (2) the effects of ionic concentration of fluid on clogging behaviors depend on the types of fine particles, and (3) fine particles prefer to accumulate along the deionized water- (DW-) CO2 interface and migrate together, which in turn easily causes clogging in pores. As a result, multiphase fluid flow during gas production from hydrate-bearing sediments could easily develop clogging in pore throats, where the relative permeability of DW-CO2 in porous media decreases. Accordingly, the relatively permeability of porous media should be evaluated by considering the clogging behavior of fines.